Prove that (cosx/1-tanx) + (sinx/1-sinx) = sinx + cosx

Expert Answers

An illustration of the letter 'A' in a speech bubbles

The trigonometric identity `cos x/(1-tanx) + sin x/(1-sinx) = sin x + cos x` has to be  proved.

If x = 45 degrees, the left hand side is equal to `oo` as `(1/sqrt 2)/(1 - 1) = 1/0 = oo` , but the right hand side is equal to `sqrt 2`

The given equation is not a trigonometric identity.

If the `1 - sin x` in the term `sin x/(1 - sin x)` is replaced with `1 - cot x` we have:

`cos x/(1-tanx) + sin x/(1-cot x)`

= `(cos x)/(1-(sin x)/(cos x)) + (sin x)/(1-(cos x)/(sin x))`

= `(cos^2 x)/(cos x - sin x) + (sin^2 x)/(sin x - cos x)`

= `(cos^2 x - sin^2x)/(cos x - sin x)`

= `((cos x + sin x)(cos x - sin x))/(cos x - sin x)`

= `cos x + sin x`

The equation `cos x/(1-tanx) + sin x/(1-sinx) = sin x + cos x` is not a trigonometric identity. `cos x/(1-tanx) + sin x/(1-cot x) = sin x + cos x` on the other hand is a trigonometric identity.

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial